Implementasi Kebijakan Pemungutan Pajak Hotel Atas Kamar Kos di Kota Bandung - Abubakar, Rodlial Ramdhan Tackbir; Ginka, Kania Risdena (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2024)
Boarding houses, one of the temporary in great-demand residences, will generate regional income (PAD) in Bandung city. This research aims to formulate an effective tax collection strategy for hotel taxes on boarding houses in Bandung City. This research employed a descriptive-qualitative method. The data collection techniques were carried out through interviews, documentation studies, and observation. Moreover, the researcher used SWOT analysis to determine the strategy formulation technique. The findings of the research demonstrated that the implementation of the hotel tax collection policy on boarding houses was consistent with the policy's standards and targets Even though the implementing agent's characteristics and the implementor's disposition had been carried out quite well, the substance of policy still contains weaknesses concerning the provisions as regards the number of rooms. Other weaknesses are as follows: The quantity of human resources are limited, relationships with other organizations are not close enough, and coordination with political elites is rarely carried out. Furthermore, social, political, and economic conditions are also less supportive at this time. The Recommended strategies are formulated using a SWOT analysis based on the results of the priority strategy which is the ST (strength-threat) strategy. Those are: organizing regular and sustainable socialization for taxpayers, building coordination between Technical Implementation Unit (UPT) and Vilage (by involving RW/ neighborhood unit), proposing changes to the content of regulations or the legal basis for hotel tax policy on boarding houses, and making a policy brief as a form of policy advocacy.